Welcome - Editorial Team, (The Toro Historical Review, 2023)
Welcome to Volume 14, Issue 1 of The Toro Historical Review! Congratulations to the authors, and a special thank you to our student editorial team who has worked hard and continued to keep us on our regular publication schedule. Thank you! This volume features five essays produced in upper division history classes and represent remarkable achievements in undergraduate research and writing. Well done!